Review of Semagystia monticola species group (Lepidoptera, Cossidae: Cossinae) with description of four new species from Central Asia - Yakovlev, Roman V.; Shapoval, Nazar A.; Shapoval, Galina N.; Naydenov, Artem E.; Pavlova, Polina D. (Altai State University, 2023)
The article gives a revision of the Semagystia monticola (Groum-Grshimaïlo, 1890) species group (Lepidoptera, Cossidae, Cossinae). The group comprises nine valid species. Detailed data on the distribution of all the species are provided. Four new species from Central Asia are described: S. churkini Yakovlev & Shapoval, sp. n. (Type locality: Kyrgyzstan, Moldo-Too Range, Kichine-Kindyk River), S. fomichevi Yakovlev & Shapoval, sp. n. (Type locality: Tajikistan, Eastern Pamir Mts., Zulumart [Palangguzar] Mt. Rg.), S. toropovi Yakovlev & Shapoval, sp. n. (Type locality: Kirgizia, Tschatkal Mt., Sary-Chelek lake), and S. uvaydo Yakovlev & Shapoval, sp. n. (Type locality: Tajikistan, Darvaz Mts., Khozratishoh Range, Khaburobot pass). The article is illustrated with imagoes of specimens from different localities and male genitalia of all new species.